PLACE-BASED EDUCATION APPROACH AS AN INNOVATION OF AN INTEGRATED CURRICULUM - fidyati sulaiman (Universitas Islam Negeri Banda Aceh, 2015)
Curriculum design is aimed to promote equality of empowerment. In most practice, however, the curriculum purposes confront conflicts especially between national and local needs. Consequently, there are many insightful and innovative educational work which has relatively small advantages for students and schools in its flexibility and opportunity. This leads to a situation in which some groups have lack of opportunities in getting benefit from the educational curriculum application. This essay presents an appproch as an innovation of an integrated curriculum called as place-based education. The significance of this strategy is believed to be able to promote the content of learning to the level of local’s relevance and engagement. Finally, the more relevant of the learning content to the students’ socio-cultural life the broader participation they can play in the community and future career.